The epidemiology of tuberculosis in cattle and humans living in the wildlife-livestock-human interface in the rural Mnisi community Mpumalanga province South Africa - Michel, Anita Luise (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2016.